Using a landscape scale to approach resources management and farm functions: the case of vanishing wooded structures and small ruminants itinerancy over the agrarian matrix - Castro, José (2012)
The agrarian policy of national governments and EU, practiced for decades, was part of a growthoriented industrialization and economic policy. This had lead, among other things, to the loss of diversified rural landscapes, which had developed in the course of history; sites and utilization, both in area and time, tend to be standardized. As a consequence, not only habitats had been lost, which is documented by an increasing number of wildlife species threatened by extinction, but also a considerable number of domestic animal and plant species have become misplaced of their natural context, in despite of some of them have been artificially maintained last decade by compensatory issues of new “environment oriented” CAP. Authors look upon two examples of threatened landscape process in three rural communities of Trás-os- Montes: (1) the vanishing punctual, linear and spatial wooded structures of agricultural matrix, and (2) the flocks’ itinerancy of native sheep and goats. In the first case, the reduction in punctual (since 1950 by -50 percent) and linear (since 1950 by -75 percent) wooded structures, as a result of functional lack such as fencing, animal forage, summer sheltering, handcraft tools, etc could have consequences in many landscape ecological process (soil loss, hydrological disturbance, seed bank removal, fragmentation, etc.). In the second case, new perennial plantations of olives and chestnuts, resulting in several constraints to animals’ circuits and forage resources availability, have disrupted traditional cereal open fields and spatial rotation. Implications for relationships of process on patterns in landscape dynamics, and incoherent consequences of financial support of some productions are discussed. The landscape scale has allowed the identification of some conflicts among environmental CAP issues for specific natural resources protection and the landscape functions in the farming system.